Pengaruh Konten Marketing Tiktok @Hazellitaa Terhadap Minat Beli Baju Dishopee - Deswita Syaputri; Sherly Devita; Ustik Listyani (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
A person's buying interest is influenced by many factors, one of which is the shopee application which is a means of marketing products with the creativity of marketing content videos that are made easily spread. The purpose of this study is to find out whether the marketing content created by Hazellitaa has an influence in increasing interest in buying clothes in the market. The population in this study was 223.1k followers of tiktok @hazellitaa, while the research sample used the Slovin technique of 100 followers. The instrument used in this study was a content marketing and purchase intention questionnaire that had been modified by the researcher. This type of research is quantitative research with Yount's (1999) approach. The data obtained were then analyzed using SPSS software. The results of the study show that marketing content on TikTok has an influence on the interest in buying clothes at Shopee. The magnitude of the effect is 50.9%, so that other factors as much as 49.1% are influenced by other variables not examined. Furthermore, the trust factor indicator has the greatest influence, namely 78.9%.